2007
DOI: 10.1002/asi.20643
|View full text |Cite
|
Sign up to set email alerts
|

Matrix comparison, Part 1: Motivation and important issues for measuring the resemblance between proximity measures or ordination results

Abstract: The present two-part article introduces matrix comparison as a formal means of evaluation in informetric studies such as cocitation analysis. In this first part, the motivation behind introducing matrix comparison to informetric studies, as well as two important issues influencing such comparisons, are introduced and discussed. The motivation is spurred by the recent debate on choice of proximity measures and their potential influence upon clustering and ordination results. The two important issues discussed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 60 publications
2
46
0
2
Order By: Relevance
“…Directed graphs can be visualized using Waldo Tobler's Flow Mapper, available at http://www.csiss.org/clearinghouse/ FlowMapper/ 3 Pajek is a software package for social network analysis and visualization which is freely available for academic usage at http://vlado.fmf. uni-lj.si/pub/networks/pajek/ matrix, supports the analytical conclusions given earlier about the expected monotonicity between these two measures (Schneider & Borlund, 2007). There are, however, some differences in the values which matter for the visualization.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Directed graphs can be visualized using Waldo Tobler's Flow Mapper, available at http://www.csiss.org/clearinghouse/ FlowMapper/ 3 Pajek is a software package for social network analysis and visualization which is freely available for academic usage at http://vlado.fmf. uni-lj.si/pub/networks/pajek/ matrix, supports the analytical conclusions given earlier about the expected monotonicity between these two measures (Schneider & Borlund, 2007). There are, however, some differences in the values which matter for the visualization.…”
Section: Resultssupporting
confidence: 86%
“…In many cases, one can expect the Jaccard and the cosine measures to be monotonic to each other (Schneider & Borlund, 2007); however, the cosine metric measures the similarity between two vectors (by using the angle between them) whereas the Jaccard index focuses only on the relative size of the intersection between the two sets when compared to their union. Furthermore, one can normalize differently using the margin totals in the asymmetrical occurrence or the symmetrical co-occurrence matrix.…”
Section: The Jaccard Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the feature matrices F T i and F Q from the ith patch of T and Q to look for matches. Inspired in part by the many studies [19], [20], [21], [22], [23], [24] which took advantage of cosine similarity over the conventional euclidean distance, we employ and justify the use of "Matrix Cosine Similarity" as a similarity measure which generalizes the cosine similarity between two vectors [25], [26], [27] to the matrix case. We illustrate the optimality properties of the proposed approach using a naive Bayes framework, which leads to the use of the Matrix Cosine Similarity (MCS) measure.…”
Section: Overview Of the Proposed Approachmentioning
confidence: 99%
“…In several earlier papers, including [25], [26], it has been shown that Pearson correlation is less discriminating than the cosine similarity due to the fact that centered values are less informative than the original values and the computation of centered values is sensitive to zero or small values in the vectors. Since the discriminative power is critical in our detection framework, we focus on the cosine similarity.…”
Section: Matrix Cosine As a Measure Of Similaritymentioning
confidence: 99%